(untitled) (Research, Society and Development, 2022)
This article has as its object the handicraft produced in the municipality of Coxim, Mato Grosso do Sul. Its objective is to analyze the social relations of handicraft production, from the category of technical organization of handicraft work. It questions the relationship between the types of handicrafts present in the municipality and the market. It points out as a hypothesis that the visibility of handicrafts is conditioned to tourism and the market strategies adopted by artisans. The theoretical framework is based on the categories of work, technical organization of artisanal work, manufacture, and merchandise. Primary sources were obtained through direct observations in the work situation at production and marketing stations, official documents, photographic records and semi-structured interviews with artisans and public managers. Secondary sources were based on scientific journals. The results show that handicraft in the municipality is manifested through the spontaneous handcraft and induced handcraft modalities (Alves, 2014). Furthermore, that despite the craftsmanship in Coxim preserving its technical base, the induced crafts modality tends to succumb due to the expansion of tourism and the manufacturing and industrial processes, which ensure the reproduction of capital.